Construction management new directions. - McGeorge, W. D.; Zou, Patrick; Palmer, Angela (Chichester, West Sussex, U.K. : John Wiley & Sons Inc., 2013)
"The construction industry faces continual challenges and demands, due to market conditions and coercion by governments, for improvements in safety, quality and cost control, and in the avoidance of contractual disputes. To meet these challenges construction enterprises need to constantly seek new directions and business models in construction management. A number of tools, methods and concepts have been developed and advocated as aids to achieving improved performance, but many in the industry find them confusing or are sceptical of their relevance. The third edition of Construction Management: New Directions brings together, in a single volume, detailed discussion of a range of contemporary management concepts which are relevant to the construction industry, including strategic management; benchmarking; reengineering; partnering and alliancing; enterprise risk management; total safety management; total quality management; value management and constructability. It provides a straightforward, accessible and objective account of these concepts, showing how they interrelate and can be used to improve the performance of the construction firm.This research based text will be essential reading for industry leaders and practitioners, as well as researchers, postgraduate and senior undergraduate students.From a review of previous editionsI am in no doubt that this book will quickly become a favourite among students and practitioners alike --Construction Manager"--
Machine generated contents note: Preface to third edition Acknowledgments Chapter 1 The culture of the construction industry The book's contents References Chapter 2 Strategic Management Introduction Overview Strategic management process Strategic management in construction Paradoxes of strategic management in construction Developing and implementing strategy in construction Change management Linking operational actions to strategy using a balanced scorecard Stakeholder identification, analysis and consultation Strategic management in action - a case study of Arup An integrated strategic management framework Conclusion References Chapter 3 Benchmarking Introduction Definition of benchmarking Historical development Types of benchmarking The process of benchmarking The benchmarking team Benchmarking Code of Conduct Legal considerations Benchmarking: the major issues Case studies Conclusion References Chapter 4 Reengineering Introduction Reengineering: what's in a name? Origins of reengineering Reengineering in a construction industry context The goals of reengineering Reengineering methodology Pitfalls of reengineering Information technology and reengineering Reengineering from a European perspective A case study of a process reengineering study in the Australian construction industry Conclusion References Chapter 5 Partnering and alliancing Introduction The origins of partnering Partnering in a construction industry context The goals of partnering Categories of partnering Project partnering Strategic or multi-project partnering Legal and contractual implications of partnering Dispute resolution Partnering: overview Project alliancing -- a natural progression from project partnering? Alliance definitions Alliancing in the construction industry The differences between alliancing and partnering Critical success factors in alliancing The financial arrangements The project outcome Postscript References Chapter 6 Enterprise Risk Management Introduction Why ERM in the construction industry? Key terms and definitions ERM principles and processes The COSO ERM AS/NZS ISO 31000 Risk Management Standard Establish objectives, context and criteria Risk identification Risk analysis and evaluation Risk response and monitoring Risk review and learning Risk communication and consultation A comparison of risk management processes ERM application techniques Implementing ERM in the construction industry Organisational culture and ERM ERM performance ERM misconceptions Relationship between ERM and strategic planning Improving ERM capability and maturity The ERM3 Model ERM3 example ERM capability improvement Project risk management (PRM) Conclusion References Chapter 7 Total Safety Management Introduction The science of safety management What is safety risk assessment at the design stage? Why safety risk assessment at design? Barriers for Implementing Safety Risk Assessment at Design Methods for safety risk assessment at design Case Study The art of safety management Components of safety culture Dimensions of safety culture Safety culture maturity models A construction safety maturity model Development of measurement criteria and survey instruments Conclusion References Chapter 8 Total quality management Introduction Definition of TQM What is quality? Historical development of TQM The need for a paradigm shift A change in the culture of the construction industry Customer focus Integration The all-embracing nature of TQM Continuous improvement Quality costs and the cost of quality Universal standards of quality such as ISO 9000 Change management The methods of TQM How to implement TQM Kaizen Current research into TQM in the construction industry Conclusion References Chapter 9 Value management Introduction Historical development Function analysis Organisation of the study Who should carry out the study? Who should constitute the team? How should alternatives be evaluated? Value management as a system The American system A case study of value management in the United States The British/European system A case study of value management in the UK 18 [24] Value management in Australia A case study of value management (and constructability) in Australia The Japanese system A case study of value management in Japan Why are the systems different? Differences in the style of management Differences in management systems The relationship between value management and quantity surveying Conclusion References Chapter 10 Constructability Introduction Origins The goals of constructability Implementing constructability Constructability in practice Constructability and the building product Constructability and Building Information Modeling (BIM) Good and bad constructability Quantifying the benefits of constructability Conclusion References Chapter 11 Linking the concepts Bibliography Index.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Construction industry -- Management; Electronic books